Oblicz wartość funkcji f dla x = 2 oraz x = -2.
a) f(x) = 3x - 2
c) f(x) = -7x-3
b) f(x) = 2x +9
d) f(x) = x² + 2
c) f(x)=x²-5
f) f(x)= -x² + x​



Odpowiedź :

a) f(2) = 3×2 - 2 = 6 - 2 = 4

f(-2) = 3 × (-2) - 2 = -6-2 = -8

c) f(2)= -7×2-3 = -14-3 = -17

f(-2)= -7×(-2)-3 = 14-3 = 11

b) f(2) = 2×2+9 = 4+9 = 13

f(-2) = 2×(-2)+9 = -4+9 = 5

d) f(2) = 2² + 2 = 4+2 = 6

f(-2) = (-2)² + 2 = -4+2 = -2

c) f(2)= 2²-5 = 4-5 = -1

f(-2)= (-2)²-5 = -4-5 = -9

f) f(2)= -2² + 2 = -4+2 = -2

f(-2)= -(-2)² + (-2) = -4-2 = -6